Dynamic spin filtering at the Co/Alq3 interface mediated by weakly coupled second layer molecules - Sanvito, Stefano; Droghetti, Andrea (My University, 2016)
Spin filtering at organic-metal interfaces is often determined by the details of the interaction between the organic molecules and the inorganic magnets used as electrodes. Here we demonstrate a spin-filtering mechanism based on the dynamical spin relaxation of the long-living interface states formed by the magnet and weakly physisorbed molecules. We investigate the case of Alq3 on Co and, by combining two-photon photoemission experiments with electronic structure theory, show that the observed long-time spin-dependent electron dynamics is driven by molecules in the second organic layer. The interface states formed by physisorbed molecules are not spin-split, but acquire a spin-dependent lifetime, that is the result of dynamical spin-relaxation driven by the interaction with the Co substrate. Such spin-filtering mechanism has an important role in the injection of spin-polarized carriers across the interface and their successive hopping diffusion into successive molecular layers of molecular spintronics devices.
PUBLISHED
Cited By :1 Export Date: 5 January 2017
Keywords: Spin filtering at organic-metal interfaces; Spin filtering at organic-metal interfaces